RELEVÂNCIA DO CANAL IÔNICO TRPV1 NO DESENVOLVIMENTO DA MALÁRIA CEREBRAL. - PEREIRA, Domingos Magno Santos (2019)
Malaria is an infectious, systemic and parasitic disease of global importance, with a high morbidity and mortality rate. Severe malaria is a neurological complication associated with brain inflammation which can lead to death or cause neurological sequelae in surviving patients. The patient's innate immune response plays a decisive role in host defense and also in the pathogenesis of cerebral malaria, since the presence of infected erythrocytes sequestered in the endothelium of the cerebral microcirculation triggers the mechanisms of the oxidative and nitrosative stress, with excessive production of reactive oxygen (ROS) and nitrogen (RNS) species, molecules related to lipid peroxidation, causing damage not only to the parasite, but also to endothelial cells and to the integrity of the blood-brain barrier, exposing then, the central nervous system to Plasmodium facliparum (in humans) and P. berghei ANKA (in rodents). Among the several changes occurring in the host in cerebral malaria, oxidative/nitrosative stress is essential for killing the parasite and signaling the immune response; in addition, the mechanism of action of several antimalarial drugs currently available targets the increase of oxidative stress, reducing parasitemia and controlling infection. In the human organism, oxidative/nitrosative stress is regulated by a group of cell membrane receptors, such as TRPV1. It was recently shown that the transient potential receptor vaniloid 1 (TRPV1), an oxidative stress sensor, modulates the peripheral immune response to malaria; however, little is known of its relevance to the cerebral changes caused in the sereve form of the disease. Therefore, the relevance of the TRPV1 in the development of cerebral malaria induced by Plasmodium berghei ANKA (1x106 infected RBCs per animal, i.p) in wild type (WT) and knockout (TRPV1KO) mice, were investigated. In another set of experiments, the use of the selective TRPV1 antagonist, SB366791, was also studied. The results show that P. berghei ANKA-induced infection significantly reduces TRPV1 expression in brain tissue. Furthermore, TRPV1 KO animals were protected against morbidity and mortality caused by cerebral malaria by attenuating the signs and symptoms of the disease as well as mortality without affecting the parasitaemia. This response was associated with reduced cerebral edema formation and modulation of gene expression of blood-brain barrier integrity markers (claudin-5 and JAM-A), as well as increased production of reactive species generated by tissue and plasma oxidative stress; and reduction in the production of systemic and cerebral cytokines. Treatment with SB366791 initiated after induction of the cerebral malaria promoted enhanced TRPV1 gene expression in the brain and increased mouse survival. Our data from the present thesis indicate for the first time that the TRPV1 ion channel contributes to the development and prognosis of cerebral malaria by modulating cerebral inflammation, therefore, it may be suggested as a therapeutic target for the treatment of Plasmodium falciparum-infected patients.